2012
DOI: 10.3892/ijmm.2012.940
|View full text |Cite
|
Sign up to set email alerts
|

Emodin inhibits tumor necrosis factor-α-induced migration and inflammatory responses in rat aortic smooth muscle cells

Abstract: Abstract. Emodin, a naturally occurring anthraquinone derivative in oriental herbal medicine, has been shown to exert a variety of pharmacological activities. The goal of this study was to determine the effects of emodin on the modulation of cell proliferation, migration, inflammatory responses, and matrix metalloproteinase (MMP)-2 and MMP-9 expression in tumor necrosis factor (TNF)-α-induced rat aortic smooth muscle cells (RASMCs). Cell proliferation and migration were measured using the MTT assay and the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Recently it was shown that emodin at a concentration of 6-100 mM (dose-relatedly) had an anti-proliferative effect on ER-over-expressing breast cancer cells and no effect on normal breast cells . Non-toxic effects for emodin have been previously reported in human vascular endothelial cells (Meng et al, 2012), and emodin did not cause a change in the growth of normal human peripheral blood mononuclear cells or in normal mice bone marrow cells (Muto et al, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Recently it was shown that emodin at a concentration of 6-100 mM (dose-relatedly) had an anti-proliferative effect on ER-over-expressing breast cancer cells and no effect on normal breast cells . Non-toxic effects for emodin have been previously reported in human vascular endothelial cells (Meng et al, 2012), and emodin did not cause a change in the growth of normal human peripheral blood mononuclear cells or in normal mice bone marrow cells (Muto et al, 2007).…”
Section: Discussionmentioning
confidence: 56%
“…Results showed that emodin significantly reduced the lipid core area and the ratio of lipid to collagen contents, down-regulated the expression of the above-mentioned inflammatory mediators and promoted PPAR-c expression and thus played a beneficial role in stabilizing VAP [27]. In rat aortic smooth muscle cells (RASMCs), emodin attenuates TNF-a induced proliferation, migration, MMP-2 and MMP-9 expression and NF-jB activation [28]. Reports have shown that emodin exerts its anti-atherogenic effects in TNFa induced human aortic smooth-muscle cell (HASMC) proliferation via caspase-and mitochondria-dependent apoptotic pathways [29,30].…”
Section: Atherosclerosismentioning
confidence: 99%
“…[27] Attenuates TNF-a-induced proliferation and migration, MMP-2 and MMP-9 expression and NF-jB activation [28] Decreases ICAM-1, IL-8, MCP-1, TNF-a, and IL-6 and phosphorylation of the p38 MAPK and IjB-a in human monocytes [30] Myocarditis Reduces serum levels of pro-inflammatory cytokines, TNF-a and IL-1b and NF-jB (p65) [ androgen-dependent transactivation of AR by inhibiting AR nuclear translocation. Furthermore, emodin decreased the association of AR and heat shock protein 90 and increased the association of AR and MDM2, which in turn induced AR degradation through proteasome-mediated pathway in a ligand-independent manner [60].…”
Section: Pancreatitismentioning
confidence: 99%
“…Emodin (1,3,8-trihydroxy-6-methylanthraquinone), a key anthraquinone derivative of Rheum palmatum, exhibits anti-inflammatory, anti-fibrotic, anti-tumor, and antiatherosclerotic effects [18,[28][29][30][31][32][33] . However, the role of emodin in TNF-α-induced apoptosis and autophagy in C2C12 myoblasts is unknown.…”
Section: Introductionmentioning
confidence: 99%